Prevalence and predictors of coronary artery disease in patients undergoing carotid artery stenting - Sulženko, Jakub; Paluszek, Piotr; Machnik, Roman; Widimský, Petr; Jarkovský, Jiří; Pieniazek, Piotr (Coronary artery disease, 2019)
INTRODUCTION: A relationship between carotid stenosis and coronary arterial disease (CAD) is widely accepted; however, data on the exact prevalence of coronary disease in patients with severe carotid stenosis are lacking. Information on the prevalence and predictors of CAD among these patients could impact diagnostic and treatment approaches. AIM: The primary aim of this study was to determine the prevalence of significant CAD among patients referred for carotid artery revascularization. The secondary objectives included characterizing the association between the level of advancement of carotid stenosis and the presence of CAD, and between atherosclerotic risk factors and the presence of CAD in patients with carotid stenosis, and also to determine whether there was a difference in the prevalence of CAD between patients with symptomatic versus asymptomatic carotid stenosis. PATIENTS AND METHODS: We included 200 patients with severe carotid stenosis, of whom 77 (38.5%) had symptomatic stenosis. All patients underwent coronary angiography no more than 6 months before the scheduled carotid revascularization. Of the 200 total of patients, 192 underwent carotid stenting, six underwent carotid endarterectomy, and two were treated conservatively. CAD was defined as stenosis of at least 50% on recent coronary angiography or a history of previous percutaneous coronary intervention and/or coronary aortic bypass graft; the prevalence was 77.5% among our patients. There was no statistically significant difference in the prevalence of CAD between patients with unilateral versus bilateral carotid stenosis or contralateral carotid occlusion. The difference in the severity of coronary disease, which was given by the SYNTAX score, was not significant between these groups. Factors associated with the presence of CAD were male sex, a history of smoking, and global or regional wall motion disorder on echocardiography. We did not find any significant difference in the prevalence of CAD between patients with symptomatic versus asymptomatic carotid stenosis. CONCLUSION: We observed a very high prevalence of concomitant CAD in patients with severe carotid stenosis. The results of our study suggest that routine preprocedural screening for CAD in patients with carotid artery stenosis could identify a large proportion of patients with silent CAD; whether treatment for CAD before carotid revascularization can prevent periprocedural myocardial infarction should be addressed in a randomized-controlled trial.
Keywords: Endovascular Procedures; hodnocení rizik; Female; Prevalence; endovaskulární výkony; Coronary Angiography; ženské pohlaví; lidé; Aged, 80 and over; Risk Assessment; koronární angiografie; stupeň závažnosti nemoci; Humans; Risk Factors; prevalence; retrospektivní studie; prospektivní studie; nemoci koronárních tepen; Carotid Stenosis; Male; Aged; Prospective Studies; stenóza arteria carotis; Stents; Coronary Artery Disease; rizikové faktory; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Severity of Illness Index; Poland; Retrospective Studies; Middle Aged; stenty; Polsko